2020
DOI: 10.1039/d0ra01645d
|View full text |Cite
|
Sign up to set email alerts
|

An inkjet-printed polysaccharide matrix for on-chip sample preparation in point-of-care cell counting chambers

Abstract: Gellan/trehalose layers were tailored to optimize on-chip storage and release of antibodies in a simple point-of-care CD4 counting chip with excellent agreement with standard methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Instead of solution mixing, the reagent can be pre-embedded into a microchip device. Zhang et al [69] reported a simple cell-counting microchip for whole blood analysis. Their microchip has a polysaccharide matrix layer of pre-embedded fluorophore-labeled antibodies capable of controlled reagent release.…”
Section: Microfluidic Chemical Conversion Techniquesmentioning
confidence: 99%
“…Instead of solution mixing, the reagent can be pre-embedded into a microchip device. Zhang et al [69] reported a simple cell-counting microchip for whole blood analysis. Their microchip has a polysaccharide matrix layer of pre-embedded fluorophore-labeled antibodies capable of controlled reagent release.…”
Section: Microfluidic Chemical Conversion Techniquesmentioning
confidence: 99%
“…The first category refers to polymer-based channels that can be fabricated using UV-curable materials. Interesting examples have been shown not only for sample distribution [113], but also in combination with novel nanomaterials to incorporate the filtration, concentration and amplification of the analyte directly within the chip before reaching the measurement point [151]. The second category refers to the fabrication of lateral-flow paper-based assays, in which the paper capillarity is exploited to guarantee the efficient flow of the sample, which is better controlled with customized hydrophilic paths printed with wax or other hydrophobic materials on paper substrates [45,152].…”
Section: Microfluidic Dispensing To Improve Repeatabilitymentioning
confidence: 99%
“…The first category refers to polymer-based channels that can be fabricated using UV-curable materials. Interesting examples have been shown not only for sample distribution [113], but also in combination with novel nanomaterials to incorporate the filtration, concentration and amplification of the analyte directly within the chip before reaching the measurement point [151]. The second category refers to the fabrication of lateral-flow paper-based assays, in which the paper capillarity is exploited to guarantee the efficient flow of the sample, which is better controlled with customized hydrophilic paths printed with wax or other hydrophobic materials on paper substrates [45,152].…”
Section: Microfluidic Dispensing To Improve Repeatabilitymentioning
confidence: 99%